Petrous Chondrosarcoma: Case Study of Two Patients with Surgical Nuances and Literature Review - Ashish Sharma; Mohit Juneja; Vandita Singh; Anil Kumar Sharma (Indian Journal of Neurosurgery)
Primary chondrosarcoma of the skull base is a malignant tumor made up of cells developed from aberrant chondrocytes that occurs in 0.1 to 0.2% of all skull base lesions. Skull base lesions are challenging not just because of their location, but also because critical local neurovascular structures are involved. Thus, we will examine two cases with varying presentations and study the literature to evaluate various surgical management options and their nuances.